Severe dengue in the early postoperative period after kidney transplantation: two case reports from Hospital Geral de Fortaleza - Maia,Samuelson Hugo Félix (2015)
Abstract: Dengue is an arbovirosis that ranges from an asymptomatic presentation to a more severe disease, which is characterized by a vascular leakage syndrome where abdominal pain is a major symptom. Transplant recipients are immunosuppressed and are less likely to develop a severe form of the disease because of a reduction in immune-mediated responses that trigger plasma extravasation events. Herein, we report two cases of severe dengue in the early postoperative period of two kidney transplant recipients. Considering the severity of the cases, we emphasize the importance of dengue screening immediately before transplantation in areas endemic for the disease.